Mengevaluasi Pembuktian Sederhana Dalam Kepailitan Sebagai Perlindungan Terhadap Dunia Usaha Di Indonesia - Dara Maghfira; Zeina Johara (LPPM Universitas Sains dan Teknologi Komputer, 2023)
MSME criteria based on Government Regulation no. 7 of 2021 concerning Ease, Protection, and Empowerment of Cooperatives and Micro, Small and Medium Enterprises, better known as PP UMKM which was issued by the government along with 48 other implementing regulations from Law no. 11 of 2020 concerning Job Creation (Job Creation Law) on 16 February 2021. The PP UMKM amended several provisions that had previously been regulated in Law no. 20 of 2008 concerning Micro, Small and Medium Enterprises (UU UMKM). One of them is the rules related to the criteria for SMEs themselves.